Investigation of Important Fatty Acids in Biofuel Production From Number of Microalgae - Taha Al-Someidae; Yousef Al-Shahery ‎; Qutaiba Al-‎Nema (College of Education for Pure Sciences, 2021)
Algae biofuels is considered as an alternative source to fossil fuels. In recent ‎decades, there was a ‎significant increase in the use of energy sources in order ‎to avoid the depletion of traditional ‎sources such as coal and petroleum. The ‎produced fuel from algal oil had important ‎characteristics compared to that ‎from other vegetable crops. This is due to the short life cycle of ‎development, ‎a fast-growing and easy to be developed. In this study, three types of micro-‎algae ‎Scendesmus dimorphus, Chlorella vulgaris and‏ ‏Chlorococcum ‎humicola‏ ‏were used and grown in in a 5 liter photobioreactor. The dry ‎biomass productivity of the three algae was estimated, and then a chemical ‎analysis ‎of the total fatty was performed to detect their biological contents as ‎well as diagnose the ‎fatty acid. Results showed that S. dimorphus produced ‎the highest levels in both biomass, 1.58 g ‎l-1 from dry weight and estimation of ‎the total fat ‎indicated C. vulgaris has the highest total fat yield, at 29.6 ‎‎%. ‎Results of fats characterization using ‎‏)‏GLC) showed that‏ ‏S. dimorphus ‎produced the high ‎percentage of saturated fatty acids for the meristic acid ‎ester (C14: 0) by 47% and the lincoseric ‎acid ester (C24: 0) was 7.194%. In ‎contrast, both Chlorella vulgaris and Chlo. humicola showed less ‎level of ‎saturated fatty acids. This indicates the suitability of algae oil derived from S. ‎dimorphus in ‎ the synthesis of fatty acid, a major source in producing ‎biofuels